Dimensi Spiritualisme Dan Humanisme Dalam Perlawanan Amir Abdelkader Hingga Gandhi Versus Kolonialisme - Asep Ahmad Arsyul; Sona Zainal Walad; Ahmad Subqi (Ma'had Aly Idrisiyyah, 2025)
Abstract Colonialism posed profound challenges to spiritual and cultural systems worldwide. Sufism, with its emphasis on peace, dialogue, and humanity, emerged as a counterforce to colonial aggression. This study examines the humanistic dimensions of Sufism through the perspectives of Amir Abdelkader and Mahatma Gandhi, both pivotal figures who embodied spiritual resistance against colonialism. The research highlights a critical gap in existing literature, which often isolates these figures without exploring their shared values and approaches. Using a comparative historical methodology, the study analyzes their paths toward mysticism, conceptualizations of the